METODOLOGI QIYAS DALAM ISTINBATH HUKUM ISLAM - arief hidayat tumanggor (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2022)
Shariah is the concrete embodiment in the middle of the community.”Even so, the Shari'ah as puts the teachings of Islam grew in a variety of situations, conditions and aspects of spacetime.” The ontological reality of Shari'ah is then gave birth to the epistemology of Islamic law (fiqh) which is basically a remotely and called the scholars with a social fact enclosing them.”These historical facts show that Islamic law (fiqh) justification of the plurality of the formulation of the law due to the role of epistemology "langage games" are different.”Islam in the middle of the progress of all fields as a result of copyright, taste as well as the work of man now this is demanded in the notice will satisfy the development of knowledge and technology. The history of the development of Islamic law have taught us that the transformation of social values, cultural, economic, and even political influence the occurrence of changes in Islamic law. Islamic law is not a unification of baku already can not interpret, but rather as a normative power that is always making, placing, treat or consider the interests of the community as the substance of the position flexibility (flexible-position), so these are not oriented for compromising notability of Islamic law. Therefore the interpretation regarding the development of science and technology as well as problems within the social reality of the community in the perspective of Islamic law is a requirement that cannot be ditwar-fresh again. Given the existence of a growing legal problems continue, being textual provisions are limited, then logically the consequences is not ijtihad can be dammed again in order to address these problems. General formulation adopted by the majority in beristinbath usually express with so-called qiyas (al-qiyas or full, al-tamtsili, al-qiyas analogy reasoning), thoughts have against an event that no provisions of the text to the other provisions of the Genesis text because there are similarities between the two illlat the law, as well as the question of the consideration of the benefit or public interest in an attempt to capture the meaning and spirit of the various provisions of the poured in religious concepts of istihsan (looking good) , istislah (seeking benefits) in this good of public benefit (al-maslaha al- amah, al-al-mursalah maslahah). The problem is nothing in its existence as one of the sources of Islamic law in the field of law science becomes one of the causes of a wide range of other causes that give rise to cross-opinion or disagreement between the scholars. Madhhab Shi'a Imamiyah and view David al-Dzahiri did not want to concede nothing to let alone receive or use it. Are among other scholars as Shi'a scholars view zaidiyyah majority and accept it as evidence of the law of the Shari'ah. Elaboration of the above turns out to be the existence of qiyas is still problematic as one source of Islamic law. Therefore, the authors are interested in research about historical perspective metodollogis in qiyas istinbath Islamic law.